Charge Transport in Magnetized Plasma - Al-Agealy, H. J. M.; Yonas, D. H.; Jawad, E. A.; Hassoony, M. A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The plasma source can restrict the motion of charges that are localizing in the non equilibrium distribution of charge energy and reducing the electrons transport across magnetic field . The electrons & ions motion are controlled by ambipolar electric field and chargeâ€“atom collision . the source density for a given electron temperature and a given ion are considered to evaluate the diffusion coefficient . the ambipolar diffusion coefficient and the cross field diffusion coefficient for charge transfer are calculated through magnetized plasma in a uniform magnetic  field , and an approximation ambipolar diffusion coefficient is evaluated. The result, showes how the diffusion process is gradually imbedded as the properties of the plasma.